Implementation of landscape ecological knowledge – achievements and challenges - Mizgajski, Andrzej; Breuste, Jürgen; Albert, Christian; Gruehn, Dietwald; Kozova, Mária; Miklós, László; Mörtberg, Ulla (My University, 2010)
This paper gives a synthetic presentation of problems related to the practical application of results in landscape ecological studies. The diagnoses presented are based on the findings of ILECO2010 symposium, which was devoted to this. The assessment considered several aspects, which determine the possibility to apply the landscape ecological knowledge. These include spatial planning, spatial management, issues related to the efficiency assessment of actions taken and collection of data essential for the decision-making process. Individual problems were complemented with conclusions of a general nature.
Keywords: IALE-Europe; landscape ecology; ILECO2010